Patterns of gender discrimination in the S&T European countries - Oliveira, L.; Carvalho, H. (2nd International RESUP Conference: Inequalities in Higher Education and Research, 2009)
Taking as a starting point the idea of a S&T European space (Oliveira, 2008), our main hypothesis is that gender discrimination in this sector is straight related with S&T development of each country or groups of countries in Europe. If this starting hypothesis would be correct, most developed S&T European regions (or spaces) should differentiate from others by having a more equalitarian gender situation. With basis on methods of multidimensional analysis we explored, in a first step, the relationships between several indicators (proportion of scientists and engineers in the total of labour force; researchers per thousand labour force and R&D expenditure in PPS per capita research) to test if there is such an heterogeneity in the S&T European space, how it is characterised and till what extent it is possible to find groups of countries with similar patterns. This analysis shows very clearly a threefold nature of the European S&T space. The most important characteristic is the division between developed (central and northern European countries) and less developed (eastern and southern European countries) S&T systems. Yet, the analysis shows another segment with peculiar characteristics, which defines a third model, typical of a few countries. In this sense it is plausible to say that we have a stratified S&T European space. Concerning gender discrimination we considered four main aspects: gender education (ISCED 6) gaps, access to the academic and research professions, working conditions, glass ceiling index and other discrimination indicators related with power positions. Exploring the statistical relations between these indicators with the S&T segments, found in the first step of our analysis, we came to the conclusion that gender discrimination exists, but it is not generalised to all indicators or S&T segments and that there are country peculiarities in gender discrimination not directly related with their position in the European S&T stratified space.